Поняття нікнейма: сутність, основні функції - Омелюх Ірина; Omelyuh Irina; Iryna Omeliukh (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Резюме. Мережеве ім’я як основний чинник самопрезентації особистості формує перше враження про користувача у віртуальному світі, стає невід’ємним складником досягнення поставленої мети. Статтю присвячено аналізові поняття нікнейм, визначенні його сутності, виокремленні характерних ознак, з’ясуванні основних функцій. Простудійовано специфіку дефініцій нікнеймав лексикографічних працях та в наукових розвідках. Визначено, що в сучасних лінгвістичних працях активно обговорюваним є питання інтернет-комунікації загалом та особливостей функціювання мовних одиниць-найменувань зокрема. Вагомим для нашого дослідження єзапропоноване в статті уточнене визначення цього поняття. З’ясовано ознаки нікнеймів, що їх вирізняє більшість дослідників: власне чи вигадане ім’я, псевдонім, прізвисько, яким послуговуються користувачі в інтернет-комунікації; місце використання –чати, форуми, блоги; місце спілкування –глобальна мережа, комунікація в інтернеті загалом.Виокремлення специфічних рис нікнеймів важливе з огляду на те, що спілкування в соціальних мережах, чатах, форумах та самопрезентація особистості в них зазнає постійних змін. У статті схарактеризовано спільні та розрізнювальні ознаки мережевого імені й таких однотипних онімів, як логінонім(у комп’ютерному дискурсі) та прізвисько, псевдонім, криптонім(в ономастиці). Спільними ознаками нікнеймата прізвиська, псевдонімає можливість утворити необмежену кількість онімів для однієї людини, приховати справжню та змоделювати вигадану особистість; нестандартність форми та вигаданість імені. Подібно до логінонімів, нікнеймиє видовими різновидами власних назв в інтернет-комунікації. Криптонім, логінонімта мережевеім’япобутують у писемній формі. У статті визначено маркаційні ознаки мережевих імен.Оскільки нікнейм –це поліфункційне явище, то в науковій розвідці окреслено функційно-семантичний потенціал нікнеймів. З’ясовано, що функції мережевих імен доцільно розподіляти залежно від місця їх використання.

A hálózati név, mint a személyiség önreprezentációjának fő tényezője, a virtuális térben az első benyomást kelti a felhasználóról, és elengedhetetlen a kitűzött célok eléréséhez. Ez a tanulmány a nickname fogalmának elemzésére összpontosít, meghatározva lényegét, kiemelve jellemző vonásait, és feltárva főbb funkcióit.A szerző áttekintette a nickname definícióinak specifikus vonásait a lexikográfiai művekben és a tudományos kutatásokban. Megállapításra került, hogy a kortárs nyelvészeti munkákban aktívan vitatott téma az internetes kommunikáció általában, és a nyelvi egységek-elnevezések funkcionálásának sajátosságai azon belül. A tanulmány számára kiemelten fontos a nickname fogalmának pontosabb definíciója.A kutatás azonosította a nickname-ek általános jellemzőit, melyek többségében megegyeznek a kutatók körében. A nickname sajátosságainak elkülönítése fontos, tekintettel arra, hogy a szociális hálózatokon, chat-eken, fórumokon való kommunikáció és a virtuális térben történő önreprezentáció folyamatosan változik. A tanulmány jellemzi a hálózati névés az olyan hasonló onimák, mint a login(a számítógépes diszkurzusban) és a becenév, álnév, titoknév(az onomasztikában) közös és megkülönböztető vonásait. A nicknameés a becenév, álnévközös vonása, hogy egy személy számára korlátlan számú onimát lehet alkotni, elrejteni a valódi identitást és kitalált személyiséget modellezni. A login-okhoz hasonlóan a nickname-ek az internetes kommunikációban a saját nevek fajtái. A titoknév, a loginés a hálózati névírásos formában létezik.A tanulmány meghatározza a hálózati nevek megjelölő jellemzőit. Mivel a nickname polifunkcionális jelenség, a tudományos kutatás rávilágít a nickname-ek funkcionális-szemantikai potenciáljára. A szerző megállapította, hogy a hálózati nevek funkcióit célszerű a használat helyszínétől függően kategorizálni.

Abstract. Network name as a primary factor in self-presentation shapes the first impression of the user in the virtual world, becoming an integral component of achieving the set goal. The purpose of this article is to analyze the concept of a nickname, defineits essence, highlightcharacteristic features, and understandits main functions.In particular, the specific characterof nickname definitions in lexicographical works and scientific research papers have been studied. It has beendetermined that contemporary linguistic works actively discuss the issue of internet communication in general and the functioning of linguistic naming units in particular. The revisedthe following characteristics of nicknames highlighted by the vast majority of researchers have been identified:definition of this concept suggested in the paper is crucial for our research. Moreover, a real or fictional name, a pseudonym, an alias utilized by users for internet communication; the place of use –chats, forums, blogs; the place of communication –the global network, communication on the internet in general.Furthermore, it is important to highlight specific features of nicknames, considering that communication in social networks, chats, forums, and self-presentation in them undergo constant changes. Therefore, this article characterizes the common and distinctive features of a network name and similaronyms as the login name (loginonyms) (presented in computer discourse), an alias, pseudonym, and cryptonym (recognized in onomastics). Common features of a nickname and an alias include the ability to create an unlimited number of onyms for one person, therefore hiding the real identity and modeling a fictional one; as well as non-conventionality of the form and fictionality of the name. Similarly tologin names (loginonyms), nicknames are specific types of proper names in the field of Internet communication. Moreover, cryptonym, login name (loginonym), and network name are used in written form. Additionally, the article defines the marking features of network names.Since a nickname is a multifunctional phenomenon, the functional-semantic potential of nicknames is outlined inthisscientificresearch. As a result, it has been revealed that the functions of network names should be categorized depending on the place of their use.
A nickname fogalma: lényege és fő funkciói
The Concept of a Nickname: Its Essence and Main Functions
https://aab-philologica.kmf.uz.ua/aabp/issue/view/5/9
Keywords: нікнейм; мережеве ім’я; віртуальне ім’я; онім; інтернет-комунікація